Evaluation of pulmonary function in Egyptian children with sickle cell disease: a single center study - Abla S. Mostafa; Dina H. Hamed; Basma B ELSayed; Amina M Kholeif; Ilham Youssry (SpringerOpen, 2024)
Abstract Background Among inherited blood diseases, sickle cell disease (SCD) is the most common, and its prevalence is rising worldwide. People with SCD often have abnormal lung function, which can lead to other health problems and a lower quality of life. This study investigated the lung function problems in Egyptian children with SCD. Methods Our study is cross-sectional analytic, held in the pediatric pulmonology and hematology specialized clinics of Abulrish Children's Hospital, Faculty of Medicine, Cairo University. A detailed history was taken; then, patients undergone spirometry. Results A total of 60 children in the steady state were recruited, 58% males and 42% females; 73% of the study population was homozygous SS, 22% was SB+thalassemia, and 5% was SB0 with a mean age of 11.4 years. Spirometry done to the patients showed that 17 of the studied 60 sickle cell patients (28%) exhibited impaired pulmonary functions primarily with a restrictive pattern (16.7%). Conclusion This study has shown that lung function problems are common in Egyptian children with sickle cell disease (SCD). Restrictive lung disease was predominant in our cohort. Therefore, regular yearly screenings using spirometry might be beneficial for early detection. Additionally, close monitoring by a pediatric lung specialist is recommended.